COMPARATIVE STUDY ON YIELD OF EDIBLE LOCAL MUSHROOM USING DIFFERENT CARRIERS OF SPAWN - Sulistiani, Rini; Hakim, Juanda; Khulidin, Khairul Asfamawi; Othman, Abu Bakar (UNIVERSITAS AL WASHLIYAH (UNIVA) MEDAN, 2025)
Spawn quality is an important factor that affects the final yield in mushroom production. As most mushroom spawns are in the form of cereals, wheat grain, sorghum and corn seeds that are used as a carrier for growth of mushroom mycelium. Inoculation of the grain spawn into media bags is an essential process. This inoculation process requires skill and focus to avoid contamination and wastage of time and material. Pellet spawn can be made by using sawdust, rice straw or wood (dowel) as carrier. This makes it simple to hold and inoculate due to its firm form instead of using grain spawn. Strains of selected edible mushrooms such as Pleurotus pulmonaris, Pleurotus florida and Schizophyllum commune are cultivated with wood pellet for mycelia colonisation. Mycelium colonisation on pellet (pellet spawn) is used for inoculation into substrate bag. The cost of pellet spawn production is 30% cheaper in mass production instead of grain spawn. The inoculation of pellet spawn into mushroom bag substrate are relatively easier and faster compared to use of grain spawn. Moreover, innoculation time on each bag could be reduced up to 40% compared with the conventional method. The production and use of pellet spawn among mushroom growers are still rare. Due to this, the use of pellet spawn is seen as an easy innoculation alternative, efficient and practical to mushroom growers.